2002
DOI: 10.1159/000065598
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Light Scattering in Rat Lenses Observed in a 2-Year Inhalation Toxicity Study

Abstract: Normal light scattering in the eye is determined primarily by the size of α-crystalline molecules. Ageing effects appear as an increase in normal lens light scattering in distinct layers. Subliminal effects of toxins on lens transparency can also cause an increase in light scattering due to protein molecule aggregation before visible opacities appear. Scheimpflug photography of the anterior eye segment with subsequent densitometric image analysis is the method of choice to evaluate such effects. To gain more i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Rats, rabbits, dogs, cats and monkeys all have ocular dimensions, which allow recording of optical sections of their eyes in a reproducible way 60 . The range of study types includes chronic applications over longer periods 61 as well as dose range studies investigating a no‐effect level with respect to lens changes. Rats have been found to be very suitable animal models in this respect, but also the rabbit can be easily documented.…”
Section: Versatility Of Scheimpflug Photography In Clinical and Expermentioning
confidence: 99%
“…Rats, rabbits, dogs, cats and monkeys all have ocular dimensions, which allow recording of optical sections of their eyes in a reproducible way 60 . The range of study types includes chronic applications over longer periods 61 as well as dose range studies investigating a no‐effect level with respect to lens changes. Rats have been found to be very suitable animal models in this respect, but also the rabbit can be easily documented.…”
Section: Versatility Of Scheimpflug Photography In Clinical and Expermentioning
confidence: 99%
“…It appears that higher ambient temperatures are associated with an increased prevalence of cataract 45. However, long-term experimental studies in rats addressing the effect of ETS exposure to the lens46 47 (exposure to SS cigarette smoke for 6 h per day, 7 days a week, for 2 years) failed to find any association between the development of cataract and exposure.…”
Section: Ets Exposure and Eye Diseasementioning
confidence: 99%
“…[7][8][9][10] However, few studies have shown the effects of DEP on the ocular mucosa. [11][12][13] Inhabitants of cities are exposed to high levels of air pollutants, including DEP, and often present irritation, burning, foreign body sensation, hyperemia, and itching in the eye. 14 They also show a reduced time of rupture of the tear film and slight damage to the surface layer of the cornea.…”
mentioning
confidence: 99%